The Implementing of Gamification in EFL Classroom at MA Baytul Mukarramah Bone (Critical Analysis on Student Academic Achievement) - Ahmad Jafar; Ambo Dalle; Arqam; Abdul Haris Sunubi; Mujahidah (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This research examines the impact of implementing gamification in learning English as a Foreign Language (EFL) at MA Baytul Mukarramah Bone. This research aims to answer the main research question regarding the effect of using wordwall gamification on student learning achievement. This research uses a qualitative approach with data collection methods through observation and interviews. Data analysis was carried out qualitatively with stages of data collection, data reduction, data presentation, and verification and conclusions. Data was obtained through observations of English teachers and interviews with students X MA Baytul Mukarramah Bone students. The research results showed that the application of wordwall.net gamification to class X MA Baytul Mukarramah Bone students was proven to be able to improve their learning achievement. This is evidenced by an increase in average exam scores and active participation of students in learning. This finding is also strengthened by the positive responses of students who show high interest in using wordwall gamification in English learning. This research provides evidence that wordwall gamification can be an effective learning strategy to improve EFL students' learning achievement at MA Baytul Mukarramah Bone. It is hoped that these findings can contribute to the development of English learning practices that are more interesting and meaningful for students.